Circulatory and Ventilatory Power: Characterization in Patients with Coronary Artery Disease - Castello-Simões,Viviane (2015)
Background:Circulatory power (CP) and ventilatory power (VP) are indices that have been used for the clinical evaluation of patients with heart failure; however, no study has evaluated these indices in patients with coronary artery disease (CAD) without heart failure.Objective:To characterize both indices in patients with CAD compared with healthy controls.Methods:Eighty-seven men [CAD group = 42 subjects and healthy control group (CG) = 45 subjects] aged 40–65 years were included. Cardiopulmonary exercise testing was performed on a treadmill and the following parameters were measured: 1) peak oxygen consumption (VO2), 2) peak heart rate (HR), 3) peak blood pressure (BP), 4) peak rate-pressure product (peak systolic HR x peak BP), 5) peak oxygen pulse (peak VO2/peak HR), 6) oxygen uptake efficiency (OUES), 7) carbon dioxide production efficiency (minute ventilation/carbon dioxide production slope), 8) CP (peak VO2 x peak systolic BP) and 9) VP (peak systolic BP/carbon dioxide production efficiency).Results:The CAD group had significantly lower values for peak VO2 (p < 0.001), peak HR (p < 0.001), peak systolic BP (p < 0.001), peak rate-pressure product (p < 0.001), peak oxygen pulse (p = 0.008), OUES (p < 0.001), CP (p < 0.001), and VP (p < 0.001) and significantly higher values for peak diastolic BP (p = 0.004) and carbon dioxide production efficiency (p < 0.001) compared with CG. Stepwise regression analysis showed that CP was influenced by group (R2 = 0.44, p < 0.001) and VP was influenced by both group and number of vessels with stenosis after treatment (interaction effects: R2 = 0.46, p < 0.001).Conclusion:The indices CP and VP were lower in men with CAD than healthy controls.